Studi Komparasi Strategi Index Card Match Dengan Snowball Throwing Terhadap Hasil Belajar Ipa Siswa Kelas Iv Sd Negeri 03 Tohudan Tahun Ajaran 2015/2016 - PRATIWI, LISA; , Drs. Mulyadi S. K., SH.,M.Pd (2016)
This study aims to determine: (1) the difference influence between Index Card Match strategy and Snowball Throwing towards natural science study result at 4th grade students SD Negeri 03 Tohudan education year 2015/2016. (2) the strategy in which more influence between Index Card Match stretegy and Snowball Throwing towards natural science study result at 4th grade students SD Negeri 03 Tohudan education year 2015/2016. This type of research is experiment research. The research was conducted one class with of 30 students. This research design including Quasi Experimental. Subject of this research is the whole 4th grade students SD Negeri 03 Tohudan. Data collection technique used is observation, interview, documentation and test. The research instrument test used is validity test with product moment correlation, while the reliability test using KR-20. Data analysis technique used prerequisite test and analysis test. Prerequesites test used is normality test with Lilliefors, while the analysis test used t-test. Based on the data analysis result 5% significant acquired value t 2,634 > t 2,002. The average value of posttest study result Index Card Match strategy with Snowball Throwing is 81,87 > 75,20. The result show that (1) there is a difference influence between Index Card Match strategy and Snowball Throwing towards natural science study result at 4th grade students SD Negeri 03 Tohudan education year 2015/2016. (2) Index Card Match strategy more influence if compared Snowball Throwing towards natural science study result at 4th grade students SD Negeri 03 Tohudan education year 2015/2016. Keyword: Learning outcomes natural science, Index Card Match, Snowball Throwing